(untitled) (Journal Of Educational and Psychological Researches, 2019)
The research aims to identify the social control among kindergarten department students. In order to achieve the objective of the research, a sample of (400) female students: (200) from Baghdad University / Faculty of Education for women and (200) from Mustansiriyha University / Faculty of Basic Education were chosen randomly. The researchers designed a tool to measure the social control of the study sample. It was exposed to group of specialists in the educational and psychological sciences, measurement and evaluation. In addition to specialists in kindergartens. Two indicators of validity were used. The Alpha-Cronbach method, Pearson correlation coefficient, and independent samples t-test were used to analyze the collected data. The findings of study revealed that research sample have a high level of social control. In the light of the research’s results, the researchers come with a number of recommendations: Emphasizing the importance of social control in the educational and educational process. Conducting an experimental study in the development of Social Control among kindergarten children.